Diversity of bacterial endosymbionts and bacteria–host co‐evolution in Gondwanan relict moss bugs (Hemiptera: Coleorrhyncha: Peloridiidae). (4th March 2013) - Kuechler, Stefan Martin; Gibbs, George; Burckhardt, Daniel; Dettner, Konrad; Hartung, Viktor
Summary Many hemipterans are associated with symbiotic bacteria, which are usually found intracellularly in specific bacteriomes. In this study, we provide the first molecular identification of the bacteriome‐associated, obligate endosymbiont in a Gondwanan relict insect taxon, the moss bugs (Hemiptera: Coleorrhyncha: Peloridiidae), which represents one of the oldest lineages within the Hemiptera. Endosymbiotic associations of fifteen species of the family were analysed, covering representatives from South America, Australia/Tasmania and New Zealand. Phylogenetic analysis based on four kilobases of 16S–23S rRNA gene fragments showed that the obligate endosymbiont of Peloridiidae constitute a so far unknown group of Gammaproteobacteria which is named here 'Candidatus Evansia muelleri'. They are related to the sternorrhynchous endosymbionts Candidatus Portiera and Candidatus Carsonella. Comparison of the primary‐endosymbiont and host (COI + 28S rRNA) trees showed overall congruence indicating co‐speciation the hosts and their symbionts. The distribution of the endosymbiont within the insect body and its transmission was studied using FISH. The endosymbionts were detected endocellularly in a pair of bacteriomes as well as in the 'symbiont ball' of the posterior pole of each developing oocyte. Furthermore, ultrastructural analysis of the Malpighian tubules revealed that most host nuclei are infected by an endosymbiotic, intranuclear bacterium that was determined as an Alphaproteobacterium of the genus Rickettsia.